2007
DOI: 10.1098/rstb.2007.2202
|View full text |Cite
|
Sign up to set email alerts
|

Climate and wildfires in the North American boreal forest

Abstract: The area burned in the North American boreal forest is controlled by the frequency of midtropospheric blocking highs that cause rapid fuel drying. Climate controls the area burned through changing the dynamics of large-scale teleconnection patterns (Pacific Decadal Oscillation/El Niñ o Southern Oscillation and Arctic Oscillation, PDO/ENSO and AO) that control the frequency of blocking highs over the continent at different time scales. Changes in these teleconnections may be caused by the current global warming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
97
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(100 citation statements)
references
References 102 publications
(168 reference statements)
3
97
0
Order By: Relevance
“…However, this variation is still constrained by the short temporal depth of the years of record in the CLDN lightning strike data set (Orville et al, 2002;Kochtubajda and Burrows, 2010). Synchronicity in major fire activity years across provinces (e.g., 1961, 2005, 2007) was consistent with several studies on fire history, suggesting that changes in forest fire activity have been observed jointly over vast areas since the 1900s (e.g., Bergeron et al, 2004b;Macias Fauria and Johnson, 2008).…”
Section: Agreements and Disagreements In Fire Activity And Forest Growthsupporting
confidence: 60%
See 2 more Smart Citations
“…However, this variation is still constrained by the short temporal depth of the years of record in the CLDN lightning strike data set (Orville et al, 2002;Kochtubajda and Burrows, 2010). Synchronicity in major fire activity years across provinces (e.g., 1961, 2005, 2007) was consistent with several studies on fire history, suggesting that changes in forest fire activity have been observed jointly over vast areas since the 1900s (e.g., Bergeron et al, 2004b;Macias Fauria and Johnson, 2008).…”
Section: Agreements and Disagreements In Fire Activity And Forest Growthsupporting
confidence: 60%
“…Multidecadal temporal changes in annual burn rates reflect the underlying influence of climate variability and extreme fire weather (Macias Fauria and Johnson, 2008;Girardin et al, 2009); these multidecadal temporal changes were well represented in the input climate data sets. An increase in temperatures and stability in precipitation between 1916 and 1924 ( Fig.…”
Section: Agreements and Disagreements In Fire Activity And Forest Growthmentioning
confidence: 97%
See 1 more Smart Citation
“…This is mainly because the Canadian boreal forest is quite large and covers different forest types, but also because both factors may not act at the same spatial scales. Previous studies showed that climate may be the first-order driver for fire on continental and subcontinental scales (Johnson 1992;Girardin 2007;Macias Fauria and Johnson 2008), mainly owing to positive 500-hPa geopotential height anomalies persisting over a given region for days (Johnson and Wowchuk 1993) and lightning strikes providing the ignition source (Flannigan and Wotton 1991). The present study showed that when fires are analysed as spatial processes taking place at the landscape level, weather related to propagation is the most important factor influencing fire size, followed by the forest fuel composition and to a lesser extent by weather conditions directly related to fire ignition (DMC).…”
Section: Discussionmentioning
confidence: 99%
“…De Simone et al (2017) investigated the effects of including PBM emitted from biomass burning, and found that this fraction is reduced to 62-71%, indicating that more mercury is deposited closer to the fires, on land, when PBM is emitted in the model. The frequency of large fires, and thus area burned, in Canada has increased in the last four decades of the 15 20 th century (Fauria and Johnson 2008). Changes in forest fires may be the greatest early impact of climate change on forests.…”
mentioning
confidence: 99%